A Portfolio Review of World Bank Rice Projects : fiscal years 1984-2011 - Pape-Christiansen, Andrea (World Bank, Washington, DC, 2016)
Rice is the world’s most heavily consumed staple crop. Its production requires enormous volumes of water and emits large quantities of atmospheric methane, a greenhouse gas some many times more powerful than carbon dioxide - particularly during a medium term period of about seven years. In a global context of growing population, increasingly scarce water resources, and climate change, more productive, sustainable, and efficient rice production warrants clear priority. The incidence of droughts associated with climate change is projected to increase in rain fed rice-growing areas, and may very well extend further into water-scarce irrigated areas. A variety of climate-smart practices and technologies are available which can move rice production towards a triple win scenario which entails increased productivity, enhanced resilience, and improved greenhouse gas mitigation. This review of World Bank projects focus on the application of sustainable principles in rice production in 172 Bank projects that were approved between 1984 and 2011. These had a total lending volume of 10.9 billion dollars. Their development outcomes are gauged based on the projects’ implementation completion reports, which also document lessons learned and results in greater detail.